Benefits of alactate training processes for elite weightlifters' training systems - Sivokhin, I. P.; Skotnikov, V. F.; Komarov, O. Y.; Tapsir, M.; Fedorov, A. I.; Kalashnikov, A. P. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to provide theoretical and practical experimental substantiations for the potential benefits of the alactate training process designed to model competitive conditions and environments. Conclusion. The experimental athletic training program with high priority being given to the alactate training tools to model the actual competitive conditions and environments as close as possible, with the relevantly focused training workload vector, makes it possible to achieve higher rates of increase in athletic performance.